A phase 3 randomized placebo-controlled trial of tadalafil for Duchenne muscular dystrophy. (24th October 2017) - Victor, Ronald G.; Sweeney, H. Lee; Finkel, Richard; McDonald, Craig M.; Byrne, Barry; Eagle, Michelle; Goemans, Nathalie; Vandenborne, Krista; Dubrovsky, Alberto L.; Topaloglu, Haluk; Miceli, M. Carrie; Furlong, Pat; et al.
Abstract : Objective: To conduct a randomized trial to test the primary hypothesis that once-daily tadalafil, administered orally for 48 weeks, lessens the decline in ambulatory ability in boys with Duchenne muscular dystrophy (DMD). Methods: Three hundred thirty-one participants with DMD 7 to 14 years of age taking glucocorticoids were randomized to tadalafil 0.3 mg·kg −1 ·d −1, tadalafil 0.6 mg·kg −1 ·d −1, or placebo. The primary efficacy measure was 6-minute walk distance (6MWD) after 48 weeks. Secondary efficacy measures included North Star Ambulatory Assessment and timed function tests. Performance of Upper Limb (PUL) was a prespecified exploratory outcome. Results: Tadalafil had no effect on the primary outcome: 48-week declines in 6MWD were 51.0 ± 9.3 m with placebo, 64.7 ± 9.8 m with low-dose tadalafil ( p = 0.307 vs placebo), and 59.1 ± 9.4 m with high-dose tadalafil ( p = 0.538 vs placebo). Tadalafil also had no effect on secondary outcomes. In boys >10 years of age, total PUL score and shoulder subscore declined less with low-dose tadalafil than placebo. Adverse events were consistent with the known safety profile of tadalafil and the DMD disease state. Conclusions: Tadalafil did not lessen the decline in ambulatory ability in boys with DMD. Further studies should be considered to confirm the hypothesis-generating upper limb data and to determine whether ambulatory decline can be slowed by initiation of tadalafil before 7 years of age. Clinicaltrials.gov identifier: NCT01865084. Classification of evidence: This study provides Class I evidence that tadalafil does not slow ambulatory decline in 7- to 14-year-old boys with Duchenne muscular dystrophy.